Synthesis and molecular modelling of thiadizole based hydrazone derivatives as acetylcholinesterase and butyrylcholinesterase inhibitory activities. Issue 3 (4th March 2022) - Işık, A.; Acar Çevik, U.; Karayel, A.; Celik, I.; Erçetin, T.; Koçak, A.; Özkay, Y.; Kaplancıklı, Z.A.
ABSTRACT: Some novel substituted thiazolylhydrazine derivatives were designed, synthesized and their inhibitory effects on acetylcholinesterase (AChE) and butyrylcholinesterase (BuChE) enzymes and antioxidant activities were investigated. The structures of the synthesized compounds were determined using different spectroscopic techniques such as 1 H-NMR, 13 C-NMR, and HRMS. According to the enzyme inhibition results, the synthesized compounds showed selectivity against BuChE enzyme inhibition. Compounds 5e, 5g, 5i and 5j displayed significant BuChE inhibition potencies. Among them, compound 5i was found to be the most effective derivative with an IC50 value of 56.01 ± 0.054 µM. In addition, their antioxidant properties were evaluated in vitro through the 2, 2-diphenyl-1-picrylhydrazyl (DPPH) assay. For compounds 5e, 5g, 5i and 5j in silico molecular docking and 100 ns molecular dynamics simulations studies against the BuChE enzyme were performed to determine possible protein-ligand interactions and stability. DFT-D3 study was performed to stabilize of compounds 5e, 5g, 5i and 5j both in gas and solvent medium and investigated their electronic properties. Of all geometries, that of DMSO is the lowest one.